Advice on weaning bronchodilators. (24th May 2012) - Sundaram, M; Chapman, J; Davenport, A; Samuels, M
Abstract : Background: Management guidelines for acute asthma suggest that children can be discharged once stable on 3-4 hourly inhaled bronchodilators.1 No standard advice is given regarding how this should be reduced back to levels indicative of well-controlled asthma. Aims: To review the advice given to parents of children admitted with acute wheezing at ward discharge on how to wean use of bronchodilators; to assess whether this improved after introduction of a discharge leaflet giving advice on weaning according to clinical severity. Methods: Questionnaires were given to: (i) parents at the time of ward discharge, and (ii) nursing and medical staff on the wards. This was done after introduction of a discharge leaflet on weaning bronchodilators developed by the respiratory team. The results were compared an earlier survey using the same questionnaire and previously reported.2 Results: Questionnaires were returned by 35 staff (75% nurses) and 25 parents after the leaflet was introduced. These were compared to the 53 staff (35% nurses) and 23 parent responses from before the leaflet was developed (tables 1 and 2 ). Conclusion: The introduction of a discharge leaflet with advice on weaning bronchodilator use in children after discharge with acute wheezing has improved the advice given by the staff and the parents understanding.